A new method to determine reflex latency induced by high rate stimulation of the nervous system - Karacan, Ilhan; Cakar, Halil I.; Sebik, Oguz; Yilmaz, Gizem; Cidem, Muharrem; Kara, Sadik; Türker, Kemal S. (Frontiers in Human Neuroscience, 2014)
High rate stimulations of the neuromuscular system, such as continuous whole body vibration, tonic vibration reflex and high frequency electrical stimulation, are used in the physiological research with an increasing interest. In these studies, the neuronal circuitries underlying the reflex responses remain unclear due to the problem of determining the exact reflex latencies. We present a novel “cumulated average method” to determine the reflex latency during high rate stimulation of the nervous system which was proven to be significantly more accurate than the classical method. The classical method, cumulant density analysis, reveals the relationship between the two synchronously recorded signals as a function of the lag between the signals. The comparison of new method with the classical technique and their relative accuracy was tested using a computer simulation. In the simulated signals the EMG response latency was constructed to be exactly 40 ms. The new method accurately indicated the value of the simulated reflex latency (40 ms). However, the classical method showed that the lag time between the simulated triggers and the simulated signals was 49 ms. Simulation results illustrated that the cumulated average method is a reliable and more accurate method compared with the classical method. We therefore suggest that the new cumulated average method is able to determine the high rate stimulation induced reflex latencies more accurately than the classical method.